Integrating surface water games into community water management toolkits: A reflection from practitioners in Odisha, India - Melesse, Mequanint B.; Duche, Vishwambhar; Guvvalavenkata, Anupama; Kumar, Dron; Sanil, Richu; Falk, Thomas; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2024)
Water is a vital resource for agricultural production, sustaining ecosystem services, and supporting livelihoods of communities. However, population growth and climate change coupled with unsustainable water use and management are increasingly pushing the limits of water resources. In many parts of India, water scarcity is already posing a threat to agricultural systems and livelihoods due to prolonged droughts and climate variability. Water scarcity is more pronounced in semi-arid and arid dryland regions of India, where the majority of these regions are characterized as high to extreme water stress areas. Effective management and governance of water resources is crucial to sustain productivity of dryland agricultural systems and livelihoods in these regions.